Casein kinase 2 specifically binds to and phosphorylates the carboxy termini of ENaC subunits - Shi, Haikun; Asher, Carol; Yung, Yuval; Kligman, Luba; Reuveny, Eitan; Seger, Rony; Garty, Haim (European journal of biochemistry, 2002)
A number of findings have suggested the involvement of protein phosphorylation in the regulation of the epithelial Na+ channel (ENaC). A recent study has demonstrated that the C tails of the β and γ subunits of ENaC are subject to phosphorylation by at least three protein kinases [Shi, H., Asher, C., Chigaev, A., Yung, Y., Reuveny, E., Seger, R. & Garty, H. (2002) J. Biol. Chem. 277, 13539–13547]. One of them was identified as ERK which phosphorylates βT613 and γT623 and affects the channel interaction with Nedd4. The current study identifies a second protein kinase as casein kinase 2 (CK2), or CK‐2‐like kinase. It phosphorylates βS631, a well‐conserved serine on the β subunit. Such phosphorylation is observed both in vitro using glutathione‐S‐transferase–ENaC fusion proteins and in vivo in ENaC‐expressing Xenopus oocytes. The γ subunit is weakly phosphorylated by this protein kinase on another residue (γT599), and the C tail of α is not significantly phosphorylated by this kinase. Thus, CK2 may be involved in the regulation of the epithelial Na+ channel.